Control Parameter Identification Method of DFIG Rotor-side Converter Considering Fault Ride-through - Chen, Jie; Duan, Jiandong; Zhu, Darui; Gao, Tong; Zhang, Yang; Cheng, Jiakang; Deng, Jun (IEEE transactions on energy conversion, 2025)
In light of the integration of large-scale wind turbine generators (WTGs) to the grid, it is very important to establish a detailed model of WTGs with consistent external characteristics of real grid-connected WTGs. However, the controller of WTGs is a 'black box' model with unknown control logic and control parameters. To address these issues, this paper establishes the detailed model through typical control logic and identification control parameters. In the fault ride-through process, the change in control logic of the WTGs controller leads to a change in control parameters. Consequently, a control parameter identification method considering fault ride-through is proposed. The control parameters are divided into normal control parameters (NCPs) and fault control parameters (FCPs), based on the operation state of the WTGs. A challenge in NCPs is the issue of low sensitivity parameter identification. The enhanced whale optimization algorithm is employed to identify NCPs, thereby achieving accurate identification of NCPs. The identification of FCPs is affected by the limiting link. Thus, the proposed identification method is based on voltage conditions division to realize the independent identification of FCPs. The proposed identification method is verified by MATLAB/Simulink and RT-LAB, and the results demonstrated that the proposed method realizes the accurate identification of control parameters.